Vegetarian Rawon Featuring Jelly Based ‘Kikil’ as an Innovation in Traditional Indonesian Cuisine - Ni Luh Kartini; Iwan Surjawan (Politeknik Internasional Bali, 2025)
Plant based foods, particularly plant based meat analogues (PBMA), have gained increasing attention as solutions to sustainability, health, and ethical challenges within global food systems. However, most PBMA innovations remain focused on generic meat substitutes and are rarely integrated into traditional culinary contexts. This study aims to develop and evaluate a vegetarian rawon using jelly based “kikil” as a sustainable innovation in Indonesian traditional cuisine. This research employed a Research and Development (R&D) approach using the ADDIE development model and was conducted in the practice laboratory of Politeknik Internasional Bali. Data were collected through observation, literature review, and sensory evaluation using a hedonic test. A total of 30 untrained panelists participated in the sensory assessment, evaluating taste, color, aroma, texture, and innovation attributes. The results indicate that the vegetarian rawon with jelly based kikil achieved good sensory acceptance, with mean hedonic scores ranging from “liked” to “highly liked”. Aroma and innovation received the highest scores, while taste and texture demonstrated acceptable performance as functional substitutes for conventional kikil. These findings suggest that plant based jelly can effectively replace gelatinous animal connective tissue in traditional dishes without compromising core sensory identity. This study contributes to the development of locally grounded PBMA by proposing a dish-based and function-driven substitution approach, while highlighting the potential of Indonesian traditional cuisine as a platform for sustainable, innovative, and market-relevant plant based food development.